Intensifikasi Ibu Hamil Dalam Mengikuti Kelas Ibu Di Wilayah Kerja Puskesmas Karangayu Kota Semarang Tahun 2022 - Nella Vallen IP; Desi Soraya (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2023)
Background: The class for pregnant women is an opportunity for pregnant women and their families to learn together about the health of pregnant women, which is carried out in groups. The holding of the Pregnant Women's Class (KIH) is implemented by providing facilities for pregnant women to study groups in the form of face-to-face meetings, and the implementation is carried out by midwives and involving all pregnant women, spouses, and/or spouses, providing increased utilization of health in maternal services in Indonesia.Objective: The purpose of this study was to describe the intensification of pregnant women participating in maternal classes in the working area of the Karangayu Health Center.Methods: The type of research used is quantitative research with descriptive methods. The population of this study was pregnant women in the working area of the Karangayu Health Center, Semarang City, in September - November 2022 and the sample used was 35 respondents who were taken using a total sampling technique.Results: The results showed that of the 35 respondents there were working mothers as many as 19 respondents (54.3%) had never participated in maternal classes, mothers who were in the second trimester of pregnancy as many as 20 respondents (57.1%) who had never participated in maternal classes and mothers who parity of more than one as many as 23 respondents (65.7%) who never participated in mother class.Conclusion: Most f the respondents never participated in classes for pregnant women due to working mothers when working with the implementation of mothers' classes colliding with each other, second-trimester mothers who lack family support, especially husbands and mothers with more than one parity due to having experience in previous pregnancies.